Disarming Nicaraguan Women: The Other Counterrevolution - Figueroa, Evelyn (Columbia Journal of Gender and Law, 1996)
Women became involved in the Nicaraguan Revolution primarily due to traditional maternal concerns. Yet, in the process of involving themselves in politics for the sake of others, they became conscious of the need to launch their own revolution and make demands for themselves as women. In part, the courage to make demands came from the sense of accomplishment and entitlement they derived from their invaluable contribution to their country. Swept away by Sandinista declarations of the right to human dignity and work, the women’s revolution was an attempt to redefine the role of Nicaraguan women, both as mothers and as women. As mothers, women wanted the same rights and privileges which men enjoyed with respect to their children, employment opportunities, and political participation. As women, they wanted the right to bear arms, to defend their country, and to exercise control over their bodies, including the right to contraceptives and abortion. During the Sandinista Revolution, women armed themselves with both physical and ideological weapons and participated at all levels. Through the Association of Nicaraguan Women Confronting the Nation’s Problems (AMPRONAC) and the Luisa Amanda Espinosa Nicaraguan Women’s Association (AMNLAE), they became politically active, undertaking consciousness-raising and educational campaigns designed to mobilize other women. Younger women became active primarily through student political and Christian organizations. Many of these women opted to participate through armed combat and joined the National Sandinista Liberation Front (FSLN).